Answer:
Option A.
Explanation:
Remainder theorem: If a polynomial P(x) divided by (x-c), then the remainder is P(c). It means if c is a root of P(x), then P(c)=0.
The given polynomial is
![f(x)=3x^3+6x^2-26x-8](https://img.qammunity.org/2019/formulas/mathematics/high-school/mzcmetyf0jqdw9293j8761qx5nc0n0h9pd.png)
Substitute x=-4 in the given polynomial.
![f(-4)=3(-4)^3+6(-4)^2-26(-4)-8](https://img.qammunity.org/2019/formulas/mathematics/high-school/iyzlqp3clgcue8kjxz1afwj71yypfmjjms.png)
![f(-4)=3(-64)+6(16)-26(-4)-8](https://img.qammunity.org/2019/formulas/mathematics/high-school/egjbgolxr712tm621d66xrqmvp0setg4jc.png)
![f(-4)=-192+96+104-8](https://img.qammunity.org/2019/formulas/mathematics/high-school/hrgp6uns2ni0sw0v20kktq39ug1dmiaw08.png)
![f(-4)=0](https://img.qammunity.org/2019/formulas/mathematics/high-school/26yi8fqyszkx31rdlau3qd9cdhfnsi1b44.png)
Similarly,
Substitute x=-2 in the given polynomial.
![f(-2)=3(-2)^3+6(-2)^2-26(-2)-8=44](https://img.qammunity.org/2019/formulas/mathematics/high-school/xo03c166yeurh841opthe9y8zua9eda4eb.png)
Substitute x=2 in the given polynomial.
![f(2)=3(2)^3+6(2)^2-26(2)-8=-12](https://img.qammunity.org/2019/formulas/mathematics/high-school/9v3vh67a6rv4x9e4s2a2np6b4sn9a8rtb0.png)
Substitute x=4 in the given polynomial.
![f(4)=3(4)^3+6(4)^2-26(4)-8=176](https://img.qammunity.org/2019/formulas/mathematics/high-school/7s4b9hof7x11e1vszrm1j3tpgbmwut6szz.png)
From the given options only at x=-4 the value of function is 0. It means remainder is 0 at x=-4.
-4 is a root of the given polynomial. Therefore the correct option is A.